Le secteur tertiaire et le développement économique régional : vers un modèle opérationnel des activités motrices - Polèse, Mario (L'Actualité économique, 1974)
AbstractTertiary activity is rapidly growing in all industrialized nations: it already accounts for almost two third of Canada's (and Québec's) total production and employment. It thus becomes increasingly reasonable to think that many service activities are becoming autonomous agents of economic growth rather than simply being induced (non-basic) activities as is generally postulated in classical regional development models. This paper discusses in what manner certain services might be involved in the growth process, and particularly how we might identify and measure them. The framework of the paper is regional rather than national growth since it is felt that it is on the regional level that the growth impact of the service sector is most easily discernible. We propose a largely conceptual model of the regional growth impact of service activities. The model leans heavily on certain theories prevalent in regional economics, especially export-base theory and central place theory. The main problem, we observe, as in all impact models, is not measuring short-run impacts but rather that of measuring long-run dynamic impacts.